The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1046/j.1365-2265.1996.617439.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone treatment affects brain neurotransmitters and thyroxine

Abstract: The study demonstrates a passage of GH from the circulation into the CSF. The observed changes in homovanillic acid and free T4 are similar to those reported after successful treatment of depressive disorders with antidepressant drugs, and may reflect a beneficial effect of GH on mood and behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 22 publications
0
76
0
Order By: Relevance
“…injections of GH (12,13). In one of these studies a dose-dependent increase in cerebrospinal fluid GH concentrations was confirmed (13).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…injections of GH (12,13). In one of these studies a dose-dependent increase in cerebrospinal fluid GH concentrations was confirmed (13).…”
mentioning
confidence: 75%
“…In one of these studies a dose-dependent increase in cerebrospinal fluid GH concentrations was confirmed (13). Further evidence for brain cells being targets for GH actions has emerged from the identification of specific receptors for the hormone in the brain (14,15).…”
mentioning
confidence: 77%
“…Other scientific approaches to this question provide supportive evidence that GH has direct effects on the CNS, affecting sleep patterns and the CSF concentrations of various neurotransmitters. The atypical nature of the depression, and the observation that GHD and its treatment does not alter CSF levels of 5HT or NE metabolites (3,4), suggests that these symptoms may not be readily amenable to conventional antidepressant medication. The results of our study suggest that patients with GH deficiency and impaired QOL and/or atypical depression should be given a trial of GH therapy, and that the effects of treatment can be gauged after only a few months.…”
Section: Discussionmentioning
confidence: 99%
“…Growth hormone treatment of GHDAs reduces the cerebrospinal fluid (CSF) concentrations of vasoactive intestinal peptide and of the dopamine metabolite, homovanillic acid (3,4), and may increase the CSF concentration of beta-endorphin (4) (although some researchers have found no effect (3)). However, GHD does not seem to alter the CSF levels of 5-hydroxytryptophan (5HT) or norepinephrine (NE) metabolites (3,4), which are usually thought to be the most significant monoamines in depression. Blunting of the GH response to provocation tests has been reported as a feature of major depression in non-GH deficient patients (5 -7).…”
Section: Introductionmentioning
confidence: 99%
“…Le Greves et al (30) suggested that GH induced the gene expression of hippocampal N-methyld-aspartate receptor in rats, coinciding with improved learning and memory capabilities. The possibility that the hormone itself may pass the blood-brain barrier is supported by several studies (31). The GH-binding receptor has been identified in the brains of humans and rats (32).…”
Section: Resultsmentioning
confidence: 64%